Konseling Paska Bencana: Telaâah atas Konsep dan Terapi Post Traumatic Stress Disorder - Dudy Imanudin, Effendi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2010)
Helping to client who suffer because of calamity victimÂ need the different specific paradigm of the public service shapes apllied in conventional approach. Service shape have character as social-psychology, stressing to urgency of socius environment and social system in helping to return psychological condition of post calamity client. The excellentÂ of thisÂ approach not only in preventive effort, promotive, rehabilitative and liberative., but also based to three ideas as: holistic human, integrated approach, humn caring and encountering nature.